Complex Horizontal Cleavage Tear Repair of the Lateral Meniscus With Fibrin Clot Augmentation - Luke V. Tollefson BS; Erik L. Slette MD; Robert F. LaPrade MD, PhD (SAGE Publishing, 2024)
Background: The menisci are critical for knee stability and cushioning and tears of the menisci have been linked to the acceleration of osteoarthritis. Horizontal cleavage tears split the meniscus into a top and bottom portion and are notoriously difficult to repair due to their localization in the avascular zone of the meniscus. Repair augmentation techniques, including fibrin clot and bone marrow venting, have been reported to increase meniscus healing. Indications: The use of a fibrin clot is indicated when there is a complex horizontal cleavage tear of the meniscus. There must be a clear separation of the top and bottom leaflets that can hold the fibrin clot inside. Technique Description: The horizontal cleavage tear is first identified, and a shaver with the suction left off is used to roughen between the upper and lower leaflets of the meniscus tear. A rasp is used inside the horizontal tear to roughen up the edges and expose the entire tear. Inside-out sutures are used in a hay bale technique to surround the tear. Thirty milliliters of blood are stirred until a fibrin clot is formed. This clot is stabilized with a circumferential Vicryl stitch and shuttled in between the leaflets of horizontal tear using a suture tied around the fibrin clot. The previously placed hay bale sutures are loosened to allow for placement of the fibrin clot. All sutures are tied at the end of the procedure. Results: A study by Nakayama et al reported a clinical success rate of 18 of 24 patients undergoing medial meniscus horizontal cleavage tear repair with fibrin clot augmentation. All patients with failures were in significant varus alignment. Another study by Kamimura et al with 10 patients reported increases in postoperative patient reported outcomes and a healing rate of 70% on second-look arthroscopy. Discussion: This fibrin clot interposition technique augments the repair of a horizontal cleavage tears. Due to horizontal cleavage tears being localized in the white-white avascular zone, augmentation including using a fibrin clot can help induce healing. This repair can help restore the stability and cushioning of the meniscus to slow the progression of osteoarthritis.